“Existia uma deusa”: o consumo midiático do Sagrado Feminino pelas mulheres residentes em ecovilas - Ferrari, Camila Tatsch (2022)
This work, through qualitative empirical research, aims to address the media consumption and social relations of women in ecovillages, with regard to gender relations and spiritual practices within their communities and in their personal experiences. The general objective of this study is to investigate how the consumption of the Sacred Feminine in the media affects gender relations in ecovillage communities. We seek to organize our theoretical framework from three axes: the current social context and alternatives based on ecovillages and a spiritual perspective; the Sacred Feminine itself as a perspective and practice adopted by women; and the Sacred Feminine from media consumption. For this, we established three axes of study: gender issues (FRASER, 2020; FEDERICI, 2017); female spirituality in ecovillages (ELLER, 2000; ARRUDA, 2018); media consumption (GARCÍA-CANCLINI, 2010). The methodology relies on the contribution of Bernard Lahire’s Sociological Portraits (2004) in order to build the trajectories of three women who have experience in ecovillages and approach the Sacred Feminine in their spirituality. In the trajectory covered, we understand that this spirituality proposes the sacralization of the female figure insofar as it attributes positive qualities and characteristics to women, contributing to female autonomy and power and, thus, indirectly to gender equality. In this sense, we conclude that it does not deconstruct patterns of gender by functioning as a support group for women and by easing conflicts between women and men only in reconciling their domestic and interests in the individual sphere.